Innovation Management to Sustain Competitive Advantage: A Qualitative Multi-Case Study - Tahat, Ghayth (Research in Business and Management, 2021)
The importance of new product development (NPD) and innovative capabilities in marketing, innovation, and business strategy has been recognized by management and researchers. Knowledge management and organizational capabilities have also been explored and evaluated by researchers and practitioners. However, the current literature shows a lack of connection between NPD, innovative capabilities, integrated shared knowledge, and organizational capabilities. Also, there is limited knowledge on the impact and the contribution of the integrated shared knowledge and the organizational capabilities to the firm’s success, performance, and sustainability. This study aimed to determine if there is a link between NPD and innovative capabilities, integrated shared knowledge, and the organization’s capability. The purpose of the research is to explore how shared knowledge and the organization’s capabilities influence and contribute to NPD, innovative capabilities, and innovative management. A qualitative, multi-site case study through one-on-one, in-depth interviews with primary decision-makers from technology and innovative companies located in Texas State in the USA is employed. The primary research question that guided the project is: How do shared knowledge and the organizational capabilities that influence NPD and innovative capability contribute to the firm’s success, performance, and sustainability? Respondent interviews have been imported and analyzed through NVivo qualitative data analytics software. Findings have been determined using NVivo 11 through theme analysis. A key finding is that shared knowledge and the organization’s capabilities are linked and critical for NPD’s success and innovative capabilities. A set of recommendations for future researchers is proposed.